Social studies and the teaching of history at senior secondary in Kabwe district, Zambia - SIMAKANDO SILONGWA (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research aimed to evaluate Social Studies and History teaching in the Kabwe District of Zambia’s Central Province. Junior high school students take a Social Studies course covering history, geography, and citizenship. There is no distinction between the three, and all are treated equally.Findings: According to the findings, the introduction of Social Studies into the Zambian curriculum has resulted in a variety of different instructional approaches. Teachers in some institutions were expected to cover all three facets of Social Studies even though they may have only received instruction in teaching one or two of these areas. It’s been my experience that in some schools, teachers teach the different parts based on their own areas of expertise. Despite its many benefits, it was discovered to have drawbacks, such as a dearth of properly trained instructors and appropriate teaching materials.Implications/Novel Contribution: This research showed that the introduction of Social Studies has negatively impacted students’ ability to perform well in history at the high school level. This is because most Social Studies teachers lack the proper credentials to teach the subject. Furthermore, government agencies failed to provide sufficient, high-quality resources for teaching. As a result, the study recommends that the government reconsider Social Studies and have extensive discussions with curriculum specialists and educators about how to best implement the subject.